The obstacle race: the fortunes of women painters and their work - Greer, Germaine (Farrar, Straus, Giroux, 1979)
If men and women are equally capable of genius, why have there been no female artists of the stature of Leonardo, Titian or Poussin? In seeking to answer this question, Germaine Greer introduces us to major but underestimated figures in the history of Western painting--Angelica Kauffmann, Natalia Goncharova, Suzanne Valadon, Berthe Morisot, Kathe Köllwitz--and produces a brilliantly incisive and richly illustrated study. She explains the obstacles as both external and surmountable and internal and insurmountable in the race for achievement.
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; arts; cours; discipline; discours dominant; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; périodes historiques; régions; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théorie de l'art

Women painters of the world: from the time of Caterina Vigri, 1413-1463, to Rosa Bonheur and the present day - Sparrow, Walter Shaw (Hacker Art Books, 1976)
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques

La jeune née - Cixous, Hélène; Clément, Catherine (Collection 10 18, 1975)
La jeune née est un texte phare du mouvement féministe moderne. Hélène Cixous et Catherine Clément y mettent en avant le concept d'écriture féminine, explorant la façon dont la sexualité et l'inconscient des femmes façonnent leur imaginaire, leur langage et leur écriture.
Keywords: 1900-1999; 1970-1979; cours; discipline; europe; fem1000; france; incontournable; littérature; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; écriture des femmes*; études culturelles; études littéraires

Le corps lesbien - Wittig, Monique (Éditions de minuit, 1973)
Le lesbianisme est traité selon une dimension poétique : le corps féminin est énuméré selon ses différentes parties, et se présente comme un manifeste de la révolte féminine, écrit par une femme, pour les femmes.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; corps; corps féminin; cours; discipline; europe; fem1000; france; lesbianisme; premier cycle; périodes historiques; régions géographiques; thématiques; études littéraires